Heat stress alleviation for dairy cows housed in an open-sided barn by cooling fan and perforated air ducting (PAD) system - Lina, Xie; Chaoyuan, Wang; Luyu, Ding; Zhiyuan, Gui; Lu, Zhang; Zhengxiang, Shi; Baoming, Li; Chuntao, Jia (International Journal of Agricultural and Biological Engineering, 2017)
Curtain-sided barns with circulation fans above stall are commonly used to house dairy cows in China. Many farms equipped with circulation fans are unable to provide appropriate cooling, especially for the naturally ventilated shed, which can result in decreasing feed intake and milk production. For alleviating heat stress and improving animal comfort, a system consisting of an air cooler and a 30 m perforated air duct (PAD) was integrated to evenly distribute cooling air. The air was cooled by underground water and delivered to targeted zones above stall bed. The system was evaluated in an open sided dairy barn in Tianjin, China. For the stalls equipped with PAD system, air velocity reached above 1.1 m/s at 0.5 m height plane of the stall space, and was more uniformly distributed. Compared to the stalls equipped with circulation fans, the PAD system lowered air temperature by 1.5°C, and increased relative humidity by 8.1%. On average, Temperature Humidity Index (THI) and Equivalent Temperature Index (ETI) were decreased by 0.5 and 0.6, respectively. After a 15 days’ operation of the system, rectal temperatures of the treated dairy cows were significantly lowered. The results also showed that the cows under PADs had a higher milk production. These findings suggest the PAD can be an effective cooling alternative for naturally ventilated dairy barns to alleviate heat stress. Keywords: dairy cow, heat stress, perforated air duct, cooling fan, naturally-ventilated barn DOI: 10.25165/j.ijabe.20171006.3135 Citation: Xie L N, Wang C Y, Ding L Y, Gui Z Y, Zhang L, Shi Z X, et al. Heat stress alleviation for dairy cows housed in an open-sided barn by cooling fan and perforated air ducting (PAD) system. Int J Agric & Biol Eng, 2017; 10(6): 1–10.